2016
DOI: 10.1039/c6ra00381h
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobically directed, catalyst-free, multi-component synthesis of functionalized 3,4-dihydroquinazolin-2(1H)-ones

Abstract: A one-pot three-component reaction of o-formyl carbamate, a primary amine, a nucleophile (1H-indole or 2-napthol) in water generated a variety of functionalised 3,4-dihydroquinazolin-2(1H)-one derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…A bunch of methods has been proposed to synthesize 3,4-dihydroquinazolinones with plausible yields. Take the examples of the multicomponent reaction (MCR) protocols investigated by Luke R. Odell et al [ 36 , 37 ], an organo-catalyzed enantioselective approach for the synthesis of chiral trifluoromethyl dihydroquinazolinones, as a biologically important scaffold, by Xie et al [ 38 ], and the catalyst-free and hydrophobically-directed approach for the production of functionalized 3,4-dihydroquinazolin-2(1H)-one by Chandrasekharam et al [ 39 ].
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…A bunch of methods has been proposed to synthesize 3,4-dihydroquinazolinones with plausible yields. Take the examples of the multicomponent reaction (MCR) protocols investigated by Luke R. Odell et al [ 36 , 37 ], an organo-catalyzed enantioselective approach for the synthesis of chiral trifluoromethyl dihydroquinazolinones, as a biologically important scaffold, by Xie et al [ 38 ], and the catalyst-free and hydrophobically-directed approach for the production of functionalized 3,4-dihydroquinazolin-2(1H)-one by Chandrasekharam et al [ 39 ].
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…26 This is a simple, highly attractive approach for accessing novel and densely substituted DHQ analogues, based on an array of different chemistries (Scheme 1). [27][28][29][30][31] During the course of our investigations on the reactivity of Nacyliminium ions (I), we observed the formation of an unknown side-product (4a) when formic acid was used as a solvent, in an aza-Henry based cyclization cascade, in lieu of acetic acid (Scheme 1). Subsequent characterization studies revealed that this compound retained the DHQ core but lacked the expected C4-substituent.…”
Section: Introductionmentioning
confidence: 99%
“…During the preparation of this manuscript, Chandrasekharam and co-workers reported a water-mediated multicomponent synthesis of 4-aryl substituted 3,4-dihydroquinazolinones under conventional heating. 24 However, it is important to highlight that the use of water as a reaction medium demanded long reaction times, and, in many cases, chromatographic purification was required, both of which detract from its appeal as a green protocol. Moreover, the scope of this method is restricted to indole and mono-functional amine nucleophiles, limiting its utility in library generation.…”
Section: Introductionmentioning
confidence: 99%